Synthesis and characterization of intrinsic CuO-ZnO semiconductor for thermoelectric cell using electrodeposition method - Nor Hairin, Assayidatul Laila; Mohd Yusaini, Nurul Batrisyia; Othman, Raihan; Mohd Salled, Mohd Faiz (UPM Press, 2023)
Among the thermoelectric materials, p-type (CuO) and n-type (ZnO) semiconductors were chosen as thermoelectric materials have much interest due to their non-toxic, abundance, balance of desirable properties, cost-effectiveness, and ease of fabrication. Ongoing research and development efforts focus on improving the thermoelectric performance of CuO-ZnO by exploring novel nanostructuring approaches, advanced doping strategies, and composite material systems. Due to their high degree of crystallinity, metal oxides have exceptional thermal stability at high temperatures and outstanding electrical conductivity. These characteristics will cause the material to improve the thermoelectric power factor (TPF), which will allow the creation of thermoelectric (TE) devices with high efficiency and high temperature. There is variety of methods to synthesize p-CuO and n-ZnO including physical vapor deposition (PVD), chemical vapor deposition (CVD), thermal oxidation and electrodeposition. In this work, we present the fabrication by simple and low-cost physical methods of both n-ZnO and p-CuO samples by using alkaline vapor oxidation, electrodeposition, and chemical bath deposition methods.